2019
DOI: 10.1136/bmjopen-2019-031053
|View full text |Cite
|
Sign up to set email alerts
|

Keep the fire burning: a survey study on the role of personal resources for work engagement and burnout in medical residents and specialists in the Netherlands

Abstract: ObjectivesThe high prevalence of burnout among medical residents and specialists raises concerns about the stressful demands in healthcare. This study investigated which job demands and job resources and personal resources are associated with work engagement and burnout and whether the effects of these demands and resources differ for medical residents and specialists.DesignIn a survey study among residents and specialists, we assessed job demands, job resources, personal resources, work engagement and burnout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 68 publications
1
24
1
1
Order By: Relevance
“…However, two studies have reported that burnout and depersonalization are more likely to occur in men rather than women [ 23 , 24 ]. Similarly, two studies have reported that burnout is more prevalent in females, though one study did have an over-representation of females [ 25 , 26 ]. Our study has shown a female preponderance in burnout and emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two studies have reported that burnout and depersonalization are more likely to occur in men rather than women [ 23 , 24 ]. Similarly, two studies have reported that burnout is more prevalent in females, though one study did have an over-representation of females [ 25 , 26 ]. Our study has shown a female preponderance in burnout and emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have also been stressed by Hariharan et al in their review that work-specific and person-specific demands are the major factors behind burnout [ 9 ]. Solms et al also reported that increased workload, work-family conflict, and lack of autonomy predispose residents to develop burnout [ 25 ]. The major triggering factors identified in our study with borderline significance is conflict between home and work and difficulty in staying on schedule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher level of psychological exibility was also shown to be associated with greater work engagement and satisfaction [44]. A study of work engagement in 124 residents and 69 experts in ve hospitals in the Netherlands reported that residents ' work engagement was associated with psychological exibility, while experts ' work engagement was associated with colleague support [45], which indicated that everyone's work engagement may be different and be affected by many factors. The hierarchical regression analysis in this study showed a signi cant positive correlation (b=0.339, p<0.001) between work engagement and psychological exibility, which was similar to the ndings of other studies [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intervention research, previous studies have linked work engagement to personal factors within health care (e.g., Fiabane et al, 2013 ). A recent article addressing psychological flexibility and work engagement among physicians ( Solms et al, 2019 ) also showed psychological flexibility to be associated with work engagement and burnout in residents but not in specialists, which implies differential challenges in work demand that should be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%